2012
DOI: 10.1111/j.1755-3768.2011.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of dry age‐related macular degeneration

Abstract: ABSTRACT.Purpose: The purpose of this study was to understand clinical significance of near-infrared reflectance (NIR), blue fundus autofluorescence (FAF) and nearinfrared autofluorescence (NIA) in dry age-related macular degeneration (AMD), by correlation with fluorescein angiography (FA) and cross-sectional spectral domain optical coherence tomography (SD OCT). Methods: We evaluated 110 eyes (62 patients, mean age: 64 ± 8 years) diagnosed with dry AMD between January 2010 and December 2010, which underwent N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 32 publications
1
62
0
Order By: Relevance
“…6,23,24 The RPE changes can be analyzed further by BAF, where the endstage areas of cell loss become hyporeflective and the surrounding border of viable cells become hyperreflective. 25,26 In the present study, we have shown that subretinal PBS or NaIO 3 induce many GA characteristic changes.…”
Section: Discussionmentioning
confidence: 99%
“…6,23,24 The RPE changes can be analyzed further by BAF, where the endstage areas of cell loss become hyporeflective and the surrounding border of viable cells become hyperreflective. 25,26 In the present study, we have shown that subretinal PBS or NaIO 3 induce many GA characteristic changes.…”
Section: Discussionmentioning
confidence: 99%
“…An exact alignment of the SD-OCT scans with the topographic cSLO images allows the examiner to correlate the in situ pathologic features observed in the OCT images to those in the angiographic images. 21 The eye tracking system ensures the precise location of the lesions in both images. The placement of calipers at various points of the Spectralis SD-OCT image allows an analysis and correlation between the 2 imaging modalities, thus confirming the precise location of the lesions, as reported by Coscas and associates.…”
mentioning
confidence: 99%
“…The capability of pvOCT imaging of the microvasculature of the choriocapillaris and the anterior choroidal vasculature has the potential to become a unique tool to evaluate therapies and understand the underlying mechanisms of age-related macular degeneration progression. ocular circulation | ocular vasculature | optical angiography | ophthalmic imaging | Fourier-domain optical coherence tomography C urrent clinical evaluation of outer retinal disease progression is accomplished with multiple imaging modalities including fundus photography, fluorescein angiography (FA), indocyanine green angiography (ICGA), fundus autofluorescence (FAF), and near infrared autofluorescence (1,2). Whereas angiography techniques are ideal to observe retinal and choroidal circulation, the lack of depth selectivity limits the ability to observe microvasculature in the choriocapillaris (CC) and the anterior choroid.…”
mentioning
confidence: 99%